â€œIslam Garis Kerasâ€ Di Mata â€œSeorang Muslimâ€ - Nur Khalik Ridwan (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2003)
This paper tries to answer some questions, namely, may Islam and other heaven religions conduct the violence in the name of peace and humanity ? may the Islamic fundamentalism conduct the terrorism for the sake of religion ? Through this paper, the writer explores that Islam prohibited the killing and terrorism for their’s contrary with the al-Qur’an and the Prophet Tradition. In the other hand the writer distinguishs terrorism in two kinds : first, the terrorism that lose the justice as the international terrorism, and second, the terrorism conducted for the implementating the Islamic Syari’at. Here, the writer gives the solution to go away from the terrorism.